Broadband multimodal THz waveguides for efficient transfer of high-power radiation in space-confined conditions. (November 2021) - Melnikov, Anatoly R.; Samsonenko, Arkady A.; Getmanov, Yaroslav V.; Shevchenko, Oleg A.; Shevchenko, Darya A.; Stepanov, Alexander A.; Fedin, Matvey V.; Yurkin, Maxim A.; Veber, Sergey L.
Highlights: Multimodal metal-coated hollow terahertz waveguides were proposed. Transmission and polarization properties were measured at 1.4, 2.3, 5.5, 33.5 THz. Transmission losses are 4.6, 6.2, 11.7 dB/m at 1.4, 5.5, 33.5 THz, respectively. Numerical simulations in COMSOL confirmed the obtained waveguides characteristics. Experimental findings were described in the framework of the geometrical optics. Abstract: Terahertz (THz) range, which lies between the microwave and infrared regions of the electromagnetic spectrum, presents a new frontier containing an abundance of technical applications and fundamental research problems. There are several challenges limiting the progress in the THz science and technology. One of them is the limited range of the guided-wave propagation of THz radiation, owing to the high loss from the finite conductivity of metals and the high absorption coefficient of dielectric materials in the THz range. In this work, we discuss the design and fabrication of multimodal hollow THz waveguides used at the X-band Electron Paramagnetic Resonance (EPR) endstation located at the Novosibirsk Free Electron Laser facility (NovoFEL). Experiments carried out at the EPR endstation are aimed to investigate the impact of THz and far infrared radiation on the spin system of different inorganic complexes and organic radicals. The EPR probehead and cryostat impose strict constraints on the possible ways of transferring the THz radiation to the sample, requiring the development, manufacturing, and characterization of specific waveguides. The proposed waveguides for X-band EPR measurements under THz radiation resemble hollow metal/dielectric waveguides. They have the shape of a hollow cylinder, tapering towards the end, with a silver-coated inner surface, and allow THz radiation to be transmitted over a distance of about 60 cm in a wide frequency range from THz to middle infrared. The waveguides performance was characterized at different frequencies of NovoFEL radiation and compared with numerical simulations. Following the requirements of polarization-sensitive EPR experiments, the waveguides were further modified by a miniature attachment, consisting of a polarizer, a semiconductor mirror, and a quarter-wave plate. The attachment allows preserving the initial polarization properties of THz radiation, turns its propagation vector, and creates the circular-polarized light irradiating the sample – all inside the limited volume of the EPR probehead.